Insight into Electrochemical CO2 Reduction on Surface-Molecule Mediated Ag Nanoparticles - Kim, Cheonghee; Eom, Taedaehyeong; Jee, Michael Shincheon; Jung, Hyejin; Kim, Hyungjun; Min, Byoung Koun; Hwang, Yun Jeong (AMER CHEMICAL SOC, 2017)
The electrochemical CO2 reduction reaction to form valued hydrocarbon molecules is an attractive process, because it can be coupled with renewable energy resources for carbon recycling. For an efficient CO2 conversion, designing a catalyst with high activity and selectivity is crucial, because the CO2 reduction reaction in aqueous media competes with the hydrogen evolution reaction (HER) intensely. We have developed a strategy to tune CO2 reduction activity by modulating the binding energies of the intermediates on the electrocatalyst surfaces with the assistance of molecules that contain the functional group. We discovered that the amine functional group on Ag nanoparticle is highly effective in improving selective CO production (Faradaic efficiency to 94.2%) by selectively suppressing HER, while the thiol group rather increases HER activity. A density functional theory (DFT) calculation supports the theory that attaching amine molecules to Ag nanoparticles destabilizes the hydrogen binding, which effectively suppresses HER selectively, while an opposite tendency is found with thiol molecules. In addition, changes in the product selectivity, depending on the functional group, are also observed when the organic molecules are added after nanoparticle synthesis or nanoparticles are immobilized with an amine (or thiol)-containing anchoring agent. CO Faradaic efficiencies were consistently improved when the Ag nanoparticle was modified with amine groups, compared with that of its thiol counterpart.
Keywords: CARBON-DIOXIDE; SILVER NANOPARTICLES; ELECTROCATALYTIC REDUCTION; SELECTIVE CONVERSION; AU NANOPARTICLES; RENEWABLE ENERGY; CATALYSTS; CAPTURE